Knowledge and practices of elderly women about fall prevention - Iara Sescon Nogueira; Jhenicy Rubira Dias; Larissa Padoin Lopes; Vanessa Denardi Antoniassi Baldissera (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective Unveil the knowledge and practices of elderly women about the prevention of falls. Methods: Qualitative, exploratory-descriptive research, developed with eight elderly women from a community group at a Basic Health Unit in the state of Paraná. Data were obtained through individual interviews, submitted to lexicographical analysis through the Descending Hierarchical Classification using the IRaMuTeQ® software, and discussed with the theoretical-analytical framework of Paulo Freire's Praxis. Results Six classes emerged: 1. Experiences, background, and practices of Health Education; 2. Advancing age as a factor for the occurrence of falls; 3. Fall prevention practices; 4. Falls and their consequences; 5. Importance of preventive practices; and 6. Environmental and behavioral risk factors in the elderly's home. Conclusion Knowledge and practices were learned from experiences, background, and educational practices in Primary Health Care, implemented in praxis and mediated by concrete reality and emancipatory dialogue.